ANALYSIS OF CHARACTER EDUCATION OF ELEMENTARY SCHOOL STUDENTS IN THE PERSPECTIVE OF PAULO FREIRE'S PHILOSOPHY OF EDUCATION - Nurhayani; Yacobus Ndona; Ibrahim Gultom (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The research carried out aims to improve the character education of elementary school students from the perspective of educational philosophy. The research used is qualitative research with a descriptive approach. Data was collected through observation, topic analysis, actions, interviews, and attitude assessment sheets. From the results found in the field, it is known that character education in elementary schools needs to be instilled and requires more special attention in order to achieve the goals of character education which are implemented appropriately. From the research results, it can be concluded that instilling character education in elementary schools is very necessary for all students regardless of level. The aim of instilling character education is to shape students into individuals who have good morals and social responsibility so that there will be no more oppression or pressure from other parties. others are in accordance with Paulo Freire's educational philosophy